Value of 18F-FDG PET/CT-Based Radiomics Nomogram to Predict Survival Outcomes and Guide Personalized Targeted Therapy in Lung Adenocarcinoma With EGFR Mutations - Yang, Bin; Ji, Hengshan; Zhong, Jing; Ma, Lu; Zhong, Jian; Dong, Hao; Zhou, Changsheng; Duan, Shaofeng; Zhu, Chaohui; Tian, Jiahe; Zhang, Longjiang; Wang, Feng; et al. (Frontiers in Oncology, 2020)
Objectives To investigate the development and validation of a radiomics nomogram based on PET/CT for guiding personalized targeted therapy in patients with lung adenocarcinoma mutation(s) in the EGFR gene. Methods A cohort of 109 (77/32 in training/validation cohort) consecutive lung adenocarcinoma patients with an EGFR mutation were enrolled in this study. A total of 1672 radiomic features were extracted from PET and CT images, respectively. The least absolute shrinkage and selection operator (LASSO) Cox regression was used to select the radiomic features and construct the radiomics nomogram for the estimation of overall survival (OS), which was then assessed with respect to calibration and clinical usefulness. Patients with an EGFR mutation were divided into high- and low- risk groups according to their nomogram score. The treatment strategy for high- and low- risk groups was analyzed using Kaplan-Meier analysis and a log-rank test. Results The C-index of the radiomics nomogram for the prediction of OS in lung adenocarcinoma in patients with an EGFR-mutation were 0.840 and 0.803 in the training and validation cohorts, respectively. Distant metastasis (hazard ratio,HR,1.80), metabolic tumor volume (MTV, HR, 1.62), and rad score (CEA, HR, 17.23) were the independent risk factors for patients with an EGFR-mutation. The calibration curve showed that the predicted survival time was remarkably close to the actual time. Decision curve analysis demonstrated that the radiomics nomogram was clinically useful. Targeted therapy for patients with high-risk EGFR mutations attained a greater benefit than other therapies (p＜0.0001), whereas the prognoses of the two therapies were similar in the low-risk group. Conclusions Development and validation of a radiomics nomogram based on PET/CT radiomic features combined with clinicopathological factors may guide targeted therapy for patients with lung adenocarcinoma with EGFR mutations. This is conducive to the advancement of precision medicine.